Death, the end of history, and beyond: Eschatology in the Bible : interpretation resources for the use of scripture in the Church - Carey, Greg (Interpretation: resources for the use of scripture in the church, 2023)
"Demonstrates how, in all its diversity, the Scriptures center hope in God's action to bring good out of evil now, in our personal journeys through death, and in visions of resurrection and justice restored"--